Achievement Children of Underprevillage Family - Ridha Husnul Hayati; Elih Sudiapermana; Sardin Sardin (IKIP Siliwangi Bandung, 2020)
This research departed from the success of children of underprevillage families on the achievement of learning achievement that they got so that one of them can graduate at Gadjah Mada University which is the number 1 college in Indonesia. Mr. X worked as a traveling fish seller using an old bicycle, while Mrs. Y looked for buds of coconut leaves to be used as a Sarang Ketupat. This study aimed to describe how the efforts of parents towards children's education, educational methods for children at home, and children's habits in learning at home. This study used qualitative research methods with the type of case study research. The data were collected by using snowball sampling technique. The participants were observed through observation and interviews. Data analysis was performed using qualitative data analysis. The process was done with data reduction, data display, and verification. After analyzing the data, it showed that: (1) parents do various ways to be able to meet the needs of family X, especially in terms of children's education; (2) the learning methods are exemplary methods, habituation, stories, and advice; (3) children- family X children have the habit of learning independently.Keywords: